Feeding Nucleotides with Corn Germ Meal or Dried Corn Distillers Grains Does Not Promote Growth Performance of Receiving and Growing Calves - M. L. DeTray; S. P. Montgomery; E. Titgemeyer; A. E. Wertz-Lutz; Christopher Vahl; A. T. Schilling; W. R. Hollenbeck; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
Corn germ meal is often used in swine and poultry diets, but very little information exists on the effects on beef cattle and on newly arrived stressed cattle. When formulating receiving and growing diets, calf health and stress are important factors to consider. Including nucleotides, an immune-boosting feed additive may aid in gastrointestinal health of an animal and furthermore improve growth performance. The objective of these experiments was to determine: 1) the effects of corn germ meal in comparison to dried corn distillers grains on growth performance and 2) the effects of nucleotides on growth performance, by receiving and growing cattle.
Keywords: receiving and growing diet; nucleotide; corn germ meal